Siltuximab (CNTO 328): a promising option for human malignancies - Chen R; Chen B (Dove Medical Press, 2015)
Runzhe Chen, Baoan Chen Department of Hematology and Oncology, Zhongda Hospital, Medical School, Southeast University, Nanjing, Jiangsu Province, People’s Republic of China Abstract: Siltuximab (CNTO 328) is a promising antibody-drug conjugate targeting cytokine interleukin-6 (IL-6). It is highly binding to IL-6 and thus neutralizing IL-6 bioactivity and promoting death of tumor cell. In this review, we mainly focus on the mechanisms, clinical studies, and adverse effect of siltuximab in the treatment of human malignancies. We also provide our recommendations for siltuximab treatment in the future. Keywords: interleukin-6, Castleman’s disease, clinical trials